William McK. Ball Revised Statutes of the State of Arkansas, Adopted at the October Session of the General Assembly of Said State, A. D. 1837, in the Year of Our Independence the Sixty-second, and of the State of Second Year Page 733-734 § 23 - (:unkn) unknown (General Publisher, 1837)
Any gun or other offensive or defensive weapon found in the possession of a slave, without having the written permission of his master the carry the same, may be seized by any person, and upon proof of such seizure before a justice of the peace of the county where the same shall have been made, such gun or weapon shall be by the order of such justice, adjudged and forfeited to the seizor for his own use, and such slave shall receive by the order of such justice, any number of stripes not exceeding thirty.
--
Keywords: CARRY - CONCEALED